The most influential factor affecting the attitudes of ESL learners in learning persuasive writing - Seow, Yi Xuan (2024)
This Final-year project (FYP) looks into how important persuasive writing is to ESL instruction and how it affects students' academic and career paths. The goal of the study is to identify the variables that affect ESL students' attitudes towards acquiring persuasive writing abilities, with an emphasis on improving curriculum design and teaching methodologies. Using a mixed-methods approach, face-to-face interviews are used to acquire qualitative insights for in-depth analysis, while digital surveys are used to collect quantitative data for wider accessibility. The data is interpreted using statistical analysis and thematic analysis, including 120 participants from Universiti Tunku Abdul Rahman (UTAR). By addressing issues and promoting a supportive, student-centred learning environment, the research helps to improve ESL instruction.